Application of a Quasi In Situ Experimental Approach to Estimate 3-D Pitting Corrosion Kinetics in Stainless Steel. Issue 13 (24th September 2016) - Almuaili, F. A.; McDonald, S. A.; Withers, P. J.; Engelberg, D. L.
Abstract : Pitting corrosion kinetics of type 304L stainless steel have been obtained using a quasi in-situ X-ray computed tomography (X-ray CT) approach. A miniature electro-chemical cell was constructed to allow imaging during potentio-dynamic polarization of a wire specimen in chloride solution. The formation of three discrete pits was observed, allowing comparison between real pit geometry and different geometrical assumptions to estimate pit growth kinetics. The pit volumes obtained by X-ray CT showed a good fit with the volume of metal dissolution calculated using Faraday's law. Large fluctuations of the mean current density were observed during the pit nucleation stage, followed by pit growth with mean current densities of 1–3 A.cm −2 . Stability products associated with these pits were on the order of 0.3–0.6 A.m −1, with a diffusivity parameter (D. ΔC) of 1.68–3.04 × 10 −8 mol.cm −1 .s −1 . Diffusion coefficients for stable pit growth of 0.83–0.96 × 10 −5 cm 2 .s −1 were estimated for metal ion concentrations of 4.2 M.